Medical Management of Heavy Menstrual Bleeding. (January 2016) - Maybin, Jacqueline A; Critchley, Hilary OD
Women with benign heavy menstrual bleeding have the choice of a number of medical treatment options to reduce their blood loss and improve quality of life. The role of the clinician is to provide information to facilitate women in making an appropriate choice. Unfortunately, many options can be associated with hormonal side effects, prevention of fertility and lack of efficacy, leading to discontinuation and progression to surgical interventions. Herein, we discuss the various options currently available to women, including antifibrinolytics, nonsteroidal anti-inflammatory preparations, oral contraceptive pills and oral, injectable and intrauterine progestogens. In addition, we describe the more novel option of selective progesterone receptor modulators and their current benefits and limitations.